The impact of information technology investment on supply chain capabilities: a review (Trans Tech Publications, 2014)
In the manufacturing industry, control of information and movement of material from suppliers at all levels is a critical matter.IT helps to manage all information among suppliers. Previous research have shown that IT has indirect effects on business performance. Moreover, there are many discussions about the capabilities and mediate the relationship between IT and business performance such as supply chain performance and supply chain process integration. The integration of dissimilar supplementary resources can produce interaction that can cause better performance.